STRATEGI PENGUATAN MODAL SOSIAL KWT NGUDI REJEKI DALAM IMPLEMENTASI KEBIJAKAN SDGS DESA DAN KETAHANAN PANGAN - Fitri Juniwati Ayuningtyas; Tanti Prita Hapsari (Jurnal Riset Daerah, 2024)
Poverty and hunger are still major issues faced by countries around the world. The Sustainable Development Goals (SDGs) policy is implemented to overcome these problems and realize a more prosperous life. This SDGs program is then passed down to the village level through the village innovation program. The target of achieving the Village SDGs in realizing villages without poverty and hunger is the government's main priority in allocating the use of village funds. This study aims to identify and analyze the problems faced by KWT Ngudi Rejeki. This type of research is descriptive qualitative with data collection techniques through interviews, observations, and documentation. The analysis method used in this study is the SWOT matrix by identifying the strategic factors of IFE and EFE. Based on the results of the analysis that has been carried out, the performance and business development strategy of KWT Ngudi Rejeki is in quadrant III so that changes in market segmentation must be made to minimize problems caused by internal factors.